2020
DOI: 10.3390/pathogens9090748
|View full text |Cite
|
Sign up to set email alerts
|

High Genotypic Diversity, Putative New Types and Intra-Genotype Variants of Bovine Papillomavirus in Northeast Brazil

Abstract: Bovine papillomavirus (BPV) can cause damage to the epithelial and mucosal tissue and currently presents 28 known types. Not all BPV types are associated with the development of cancer in cattle. Studies have shown that variants of human papillomavirus types can present different pathogenic profiles. However, despite the similarity, it is not yet known whether variants of BPV types can also present varying degrees of pathogenicity. Thus, the aim of this study was to evaluate the genetic variability of BPV type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(84 reference statements)
1
3
0
Order By: Relevance
“…Additionally, 40% similarity between the detected type BPV42 was found with two human papillomaviruses isolated from healthy skin (GenBank number: KC752024.1) and cases associated with epidermodysplasia verruciformis in children (GenBank number: AY044281.1), respectively, coming from China and France [48]. In our study, a new putative BPV type was found (isolate PL-25), showing 75% similarity with already registered in GenBank database isolates BPVUFSBR-45 (GenBank number: MT674614.1) and BPVUFSBR-34 (GenBank number: MT674603.1), isolated in Brazil by Figueirêdo et al [47]. These isolates were phylogenetically closer to type 25, but PL-25 shows more correlation with the so called type BPV43 and may potentially belong to the Epsilonpapillomavirus genera (Figure 5).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, 40% similarity between the detected type BPV42 was found with two human papillomaviruses isolated from healthy skin (GenBank number: KC752024.1) and cases associated with epidermodysplasia verruciformis in children (GenBank number: AY044281.1), respectively, coming from China and France [48]. In our study, a new putative BPV type was found (isolate PL-25), showing 75% similarity with already registered in GenBank database isolates BPVUFSBR-45 (GenBank number: MT674614.1) and BPVUFSBR-34 (GenBank number: MT674603.1), isolated in Brazil by Figueirêdo et al [47]. These isolates were phylogenetically closer to type 25, but PL-25 shows more correlation with the so called type BPV43 and may potentially belong to the Epsilonpapillomavirus genera (Figure 5).…”
Section: Discussionsupporting
confidence: 73%
“…In our study, for the first time, infections caused by type 25 and the so called types BPV42 (potentially classified to the Xipapillomavirus genus) and BPV43 (potentially classified to the Epsilonpapillomavirus genus) were found in cows in Europe. Outcomes of these types were only reported before in Brazil from cases of teat papillomatosis of milking cows (GenBank: MG252779.1), with low prevalence [4,47]. Macroscopic features of lesions caused by these types have not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no evidence that BPV13 causes equine sarcoids in any country other than Brazil [9]. However, the detection of this PV type in bovine tissues from Brazil, Italy, and China suggests that BPV13 may have a more global distribution than previously recognized [20][21][22]. There is currently no evidence that BPV14 or OaPV2 causes equine sarcoids.…”
Section: Discussionmentioning
confidence: 99%
“…BPV has been associated with economic losses in several countries, such as Brazil, Italy, Iraq, the United States, Japan, and Germany. [5][6][7][8][9] In Brazil, the virus was found in at least 9 states, 2,[10][11][12][13][14][15][16][17][18][19][20] and makes the commercialization of cattle more difficult due to its unpleasant sight, leather deprecation, and some degree of infertility. 13,16 Females will also suffer from mild to severe milk production incapacitation and/or painful milking.…”
Section: Introductionmentioning
confidence: 99%